2004
DOI: 10.1186/1475-9276-3-3
|View full text |Cite
|
Sign up to set email alerts
|

The Oslo Health Study: The impact of self-selection in a large, population-based survey

Abstract: Epidemiological studiesequityhealth surveysnon-responseresponse biasself-selectionbiasethnicityresponse ratedisability benefit. AbstractBackground: Research on health equity which mainly utilises population-based surveys, may be hampered by serious selection bias due to a considerable number of invitees declining to participate. Sufficient information from all the non-responders is rarely available to quantify this bias. Predictors of attendance, magnitude and direction of non-response bias in prevalence estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
379
6
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 415 publications
(436 citation statements)
references
References 40 publications
42
379
6
9
Order By: Relevance
“…Participants were older and more likely to have a high education, and more women than men participated [33]. This conforms well with other studies, which have found that participation rates generally increase with age, female gender and higher education level [65]. The difference between respondents and non-respondents presents a socio-economic gradient that may have influenced the prevalence estimates of interpersonal violence and adult mental health problems.…”
Section: Discussionsupporting
confidence: 85%
“…Participants were older and more likely to have a high education, and more women than men participated [33]. This conforms well with other studies, which have found that participation rates generally increase with age, female gender and higher education level [65]. The difference between respondents and non-respondents presents a socio-economic gradient that may have influenced the prevalence estimates of interpersonal violence and adult mental health problems.…”
Section: Discussionsupporting
confidence: 85%
“…The response rate was, however, low, which may have induced a selection bias and reduced the external validity. However, a Norwegian study on non-responders found no evidence of major systematic errors [23]. This study had many parallels with our study with regard to time, design, and response rate.…”
Section: Discussionsupporting
confidence: 80%
“…Although the attendance to the health survey was lower than desired, the impact of self-selection in a similar large population-based Norwegian survey was judged to have little impact on the results (Sogaard et al, 2004). The inclusion of only those with IBS and 'alarm symptoms' was done for capacity reasons, and might have induced a bias.…”
Section: Discussionmentioning
confidence: 99%